Comparison between a flash glucose monitoring system and a portable blood glucose meter for monitoring dogs with diabetes mellitus. (30th October 2020) - Del Baldo, Francesca; Canton, Claudia; Testa, Silvia; Swales, Harry; Drudi, Ignazio; Golinelli, Stefania; Fracassi, Federico
Abstract: Background: Flash glucose monitoring system (FGMS; FreeStyle Libre) was recently validated for use in diabetic dogs (DD). It is not known if this system is clinically useful in monitoring DD. Objective: To compare the clinical utility of FGMS against blood glucose curves (BGCs) obtained with a portable blood glucose meter (PBGM) in monitoring DD. Animals: Twenty dogs with diabetes mellitus. Methods: Prospective study. Dogs with diabetes mellitus on insulin treatment for at least 1 month were included. Comparisons of insulin dose recommendations based on the in‐hospital GCs acquired using FGMS and a PBGM, consecutive‐day interstitial GCs (IGCs) acquired at home using the FGMS, and consecutive‐day, home vs hospital IGCs acquired using the FGMS were made using concordance analysis. Results: There was good concordance between insulin dose recommendations based on FGMS and PBGM generated GCs and IGCs obtained in the 2 different environments on 2 consecutive days, but almost absent concordance between IGCs obtained on 2 consecutive days at home. Glucose nadirs were detected in 34/43 (79%) of Ambulatory Glucose Profile (AGP) reports of the FGMS. In comparison, concordant glucose nadirs were identified in 14/34 (41%) BGCs using PBGM. The individual FGMS scans and PBGM identified 60% and 9% of low IG/hypoglycemic episodes, respectively. Conclusions and Clinical Importance: Insulin dose adjustments based on BGCs can be suboptimal. The FGMS allows a more accurate identification of the glucose nadirs and hypoglycemic episodes compared to the use of a PBGM and assessment of day‐to‐day variations in glycemic control.